Inferior Oblique Myectomy versus Anterior and Nasal Transposition for Superior Oblique Muscle Palsy (preliminary report) (Journal of Pharmaceutical Negative Results, 2023)
Background: Objective: To evaluate the effect of inferior oblique Anterior and Nasal transposition procedure and myectomy as treatment options for superior oblique palsy. Methods and Analysis: 20 patients were classified into two groups. Group A included 10 patients underwent anterior and nasal transposition (ANT) of inferior oblique muscle (2mm × 2mm nasal and posterior to inferior rectus insertion). Group B 10 patients who underwent inferior oblique myectomy. Results: In ANT group, the vertical deviation improved in primary position postoperative versus 16.7 ± 1.6 in right eye/18 ± 2 in left eye preoperative. In myectomy group, the vertical deviation improved in primary position versus 13.3 ± 3.5 in right eye/12 ± 2 in left eye preoperative . Conclusion: The results of both groups are satisfactory as surgical treatment options to SOP with accepted success rates.